PENGARUH KOMPETENSI SDM, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PELAYARAN PENGANGKUT BATU BARA KOTA BANJARMASIN - Abdul Mu'minin; Muhammad Alfani; Sulastini sulastini (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
This research aims to; (1) Empirically examine the effect of human resource competence to employee performance on the shipping coal carrier company (2) empirically examine the influence of organizational culture on employee performance on the shipping coal carrier company (3) empirically examine the influence of leadership style on the performance of employee at the shipping coal carrier company (4) empirically examine the effect of simultaneously human resource competence, organizational culture and leadership style on employee performance on the shipping coal carrier company. This research using quantitative methods approach to examine the sample, using the formula Slovin then obtained 157 samples from the total population of 258, and a questionnaire as a tool for collecting data given to a random sample of respondents and instruments research was made using a Likert scale of 1-5. All the collected data were processed using SPSS version 21. Based on the analysis using SPSS v21 then the conclusion can be drawn in four hypotheses, namely the human resource competence, organizational culture and leadership style simultaneously giving significant effect on employee performance, human resource competency partially giving significant effect on employee performance, organizational culture has no significant effect on the performance of employees performance, leadership style partially significant effect on employee performance. Keywords: Human resource Competence, Organizational Culture and Leadership Style, Employee Performance